DRAPA trial--closed-suction drains versus closed gravity drains in pancreatic surgery: study protocol for a randomized controlled trial - Čečka, Filip; Loveček, Martin; Jon, Bohumil; Skalický, Pavel; Šubrt, Zdeněk; Ferko, Alexander (Trials, 2015)
BACKGROUND: The morbidity of pancreatic resection remains high, with pancreatic fistula being the most common cause. The important question is whether any postoperative treatment adjustment may prevent the development of clinically significant postoperative pancreatic fistulae. Recent studies have shown that intraabdominal drains and manipulation using them are of great importance. Although authors of a few retrospective reports have described good results of pancreatic resection without the use of intraabdominal drains, a recent prospective randomized trial showed that routine elimination of drains in pancreaticoduodenectomy is associated with poor outcome. An important issue arises as to which type of drain is most suitable for pancreatic resection. Two types of surgical drains exist: open drains and closed drains. Open drains are considered obsolete nowadays because of frequent retrograde infection. Closed drains include two types: passive gravity drains and closed-suction drains. Closed-suction drains are more effective, as they remove fluid from the abdominal cavity under light pressure. However, some surgeons believe that closed-suction drains represent a potential hazard to patients and that negative pressure might increase the risk of pancreatic fistulae. Nobody has yet specifically dealt with the question of which kind of drainage is most appropriate in pancreatic surgery. METHODS/DESIGN: The aim of the DRAins in PAncreatic surgery (DRAPA) trial is to compare the closed-suction drain versus the closed passive gravity drain in pancreatic resection. DRAPA is a dual-centre, prospective, randomized controlled trial. The primary endpoint is the rate of postoperative pancreatic fistula; the secondary endpoint is postoperative morbidity with follow-up of 3 months. DISCUSSION: No study to date has compared different types of drains in pancreatic surgery. This study is designed to answer the question whether any particular type of drain might lower the rate of postoperative pancreatic fistula or other complications. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01988519. Registered 13 November 2013.
Keywords: Pancreatectomy; pankreatektomie; Humans; Equipment Design; Gravitation; rizikové faktory; Pressure; tlak; výsledek terapie; lidé; odsávání; pankreatoduodenektomie; časové faktory; Pancreatic Fistula; klinické protokoly; gravitace; pankreatická píštěl; Treatment Outcome; design vybavení; Czech Republic; výzkumný projekt; Pancreaticoduodenectomy; drenáž; Research Design; Suction; Clinical Protocols; Česká republika; prospektivní studie; Time Factors; Drainage; Risk Factors; Prospective Studies